Some Factor VIII (FVIII) Inhibitors Recognise a FVIII Epitope(s) that Is Present only on FVIII-vWF Complexes - Gilles, Jean Guy G.; Lavend’homme, Renaud; Peerlinck, Kathelijne; Jacquemin, Marc G.; Hoylaerts, Marc; Jorieux, Sylvie; Mazurier, Claudine; Vermylen, Jos; Saint-Remy, Jean-Marie R. (Thrombosis and Haemostasis, 1999)
A mild haemophilia A patient (LE) with an Arg2150His mutation in the C1 domain of the factor VIII (FVIII) light chain was shown to have anti-FVIII antibodies inhibiting wild type but not self FVIII. Polyclonal anti-FVIII antibodies of this patient were purified by affinity adsorption using recombinant FVIII (rFVIII) and/or plasma-derived FVIII-von Willebrand factor (vWF) complexes. A distinct population of antibodies was obtained that bound to FVIII-vWF complexes but not to rFVIII, indicating that an epitope was created by the association of FVIII to vWF. Such antibodies belonged to the IgG2 isotype, but the FVIII epitopes to which they bind could not be mapped with precision due to vWF dependency. Depletion experiments showed that anti-FVIII antibodies recognising FVIII-vWF complex also distinguished wild-type from mutated self FVIII, indicating that the Arg2150His mutation alters the B cell epitope formed by the association of FVIII to vWF. To determine whether the Arg2150His substitution also alters the formation of the FVIII-vWF complex, the interaction between mutated or normal FVIII with vWF was evaluated in plasma. The dissociation rate of mutated FVIII from vWF was found to be significantly increased. The presence of an Arg2150His mutation therefore results in the disappearance of a FVIII B cell epitope generated by the association of FVIII with vWF. Patients carrying such an Arg2150His mutation and receiving infusion of wild-type FVIII may therefore be at risk of developing inhibitors to allogeneic FVIII only.